Mitigation of high voltage induction effect on ICCP system of gas pipelines: a field case study - Rohana Ismail; Arnawan Hasibuan; Muzamir Isa; Faizar Abdurrahman; Nurul Islami (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
An analysis of the high voltage induction effect on the impressed current cathodic protection (ICCP) system on pipelines parallel toward high voltage power lines was employed in this research. Mitigation of high voltage effect throught human and environment is necessary to implemented. Direct current induction was used to increase the electrical potential of the gas pipeline, from Klumpang to sicanang area, Indonesia. During the mitigation process, the highest induction value was obtained 0.00574 KV which is previously was 0.01732 KV, and occurred at the limit of the allowable secure touch tension value of 0.015 KV. The data that acquire from the measurement of test point of ICCP underneath the transmission line revealed a comparison data between field measurements occurred of mitigation process. The direct current induction method is found to be safe for ICCP system and environment.